Intraspecific Inversion in psbA-trnH Region and its Implication for DNA Barcoding: Case Study of Capparis spinosa L. Group - Maryam Ahmadi; Hojjatollah Saeidi; Seyed Mansour Mirtadzadini (تاکسونومی و بیوسیستماتیک, 2019)
DNA barcoding is one of the developing methods in molecular systematics for the identification of species. psbA- trnH is one of the most variable noncoding regions of chloroplast genome and a standard DNA barcode for plant species. However, intraspecific inversions limited the ability of this barcode in the identification of species. The efficiency of these structural changes in the identification of Capparis spinosa genre, including C. spinosa, C. parviflora, C. mucronifolia and C. cartilaginea, was investigated in the present study. Twenty five sequences from 4 species of this complex and 3 other species of the genus Capparis was aligned. The results revealed intraspecific polymorphism in 2 regions of psbA-trnH (8% of whole region) in this group. Analysis of data showed that ignoring these inversions has led to overestimating intraspecific divergence, underestimating interspecific divergence, and disability of psbA-trnH in the identification of closely related taxa. Using reverse complementary sequence may partly overcome this problem. Based on the results of this study, it can be recommended that sampling from a wide geographic range of a species would reveal more intra-specific molecular variation and increase the efficiency of a DNA barcode. Key words: Capparis Spinosa, Intraspecific Inversion, psbA- trnH Region.